Effect of parameters on 3D printing of alumina ceramics and evaluation of properties of sintered parts. Issue 3 (3rd July 2021) - Mamatha, Sirisala; Biswas, Papiya; Ramavath, Pandu; Das, Dibakar; Johnson, Roy
ABSTRACT: Paste rheology and printing parameters contribute to a great extent to engineer the properties of ceramic parts produced through 3D printing process. Alumina paste, which showed shear thinning behavior, was prepared using optimum concentration of additives. Paste was 3D printed and effect of printing parameters such as printing speed, length to diameter (L/D) ratio of nozzle, self-standing distance of extrudate, filling pattern and filling angle have been studied. Additionally, effect of the substrate material on which the extrudate is printed was also elucidated. A printing speed of 5–6 mm/s, an L/D ratio of 25 mm and self-standing distance of 1.25 ± 0.25 mm are found to be optimum. Further, a filling pattern of rectilinear geometry along with filling angle of 90° is found to be desirable. Out of the substrates evaluated, polished metal surface is found to be relatively better to achieve close tolerances. The alumina samples printed under optimized conditions are found to possess integrity with respect to the structure and close to pre-designed dimensions. Sintered samples were found to be free of crack and exhibited a density of 3.88 g/cc (97.5% of theoretical density). Density and hardness (16.5 GPa) of printed part correlates well with the microstructure consisting of grains of average size of 9.68 μm.